Investigating the types and causes of slips of the tongue of one of the Indonesian female singers - Anggun Harastasya; Dadang Sudana; Ruswan Dallyono (Universitas Pendidikan Indonesia (UPI), 2020)
A slip of the tongue is one of the speech errors that often encounter in everyday life. Many people may have experienced this phenomenon either consciously or not. However, it would be different when a public figure made slips of the tongue. One of the Indonesian female singers has been viral on social media because of slips of the tongue that she made. She frequently made slips of the tongue when speaking in front of people. Thus, the study is conducted to investigate the phenomenon of slips of the tongue of this singer by revealing the mistakes found in the process of the articulatory program of her utterances, the dominant types of slips of the tongue used by her, and the causes of slips of the tongue. Furthermore, the study is based on a qualitative case study. The data were obtained by downloading three YouTube videos that contained the compilation video of slips of the tongue by the singer and her interview video with Sarah Sechan Talk Show as well as Narasi Entertainment’s Podcast. The transcriptions of the three videos became the source of the data. The study uses the theory from Garrett (1975) about the process of the articulatory program and Clark and Clark (1977) about types of slips of the tongue and factors of speech error. This study also uses the theory from Carroll (1986) about other types of slips of the tongue which are addition and deletion to analyze the data. This study has revealed that this Indonesian female singer mostly made mistakes in the process of phonetic segments as many as 33 times. It was also found that substitution is the dominant type of slips of the tongue that used in the video, as many as 22 times. Moreover, the causes of slips of the tongue were cognitive difficulty and social factors. Keywords: Speech error; slips of the tongue; one of the Indonesian female singers.